A Review on the Hydroisomerisasion of n-Parafins over Supported Metal Catalysts - Muhammad Safaat; Indri Badria Adilina; Silvester Tursiloadi (Jurnal Rekayasa Proses, 2021)
Catalytic hydroisomerization of n-paraffin aims to produce branched paraffin isomers and suppress cracking reactions in the production of the low cloud point of biodiesel. The development of the type of metal and catalyst support, amount of metal loading, and reaction conditions are important to increase the catalyst activity. A high performace catalyst for hydroisomerization bears bifunctional characteristics with a high level of hydrogenation active sites and low acidity, maximizing the progress of hydroisomerization compared to the competitive cracking reaction. In addition, a catalyst support with smaller pore size can hinder large molecular structure isoparaffins to react on the acid site in the pore thus providing good selectivity for converting n-paraffin. Catalysts loaded with noble metals (Pt or Pd) showed significantly higher selectivity for hydroisomerization than non-noble transition metals such as Ni, Co, Mo and W. The reaction temperature and contact time are also important parameters in hydroisomerization of long chain paraffin, because long contact times and high temperatures tend to produce undesired byproducts of cracking. This review reports several examples of supported metal catalyst used in the hydroisomerization of long chain hydrocarbon n-paraffins under optimized reaction conditions, providing the best isomerization selectivity results with the lowest amount of byproducts. The role of various metals and their supports will be explained mainly for bifunctional catalysts.